New species of Trachycorystes Bleeker, with comments on other species of the genus (Ostariophysi: Siluriformes: Auchenipteridae) - Heraldo A. Britski; Alberto Akama (Neotropical Ichthyology)
A new species of Trachycorystes from the rio Aripuanã, above Dardanelos and Andorinhas falls, is described. The new species is distinguished from the only other species of the genus, T. trachycorystes, by the following characteristics: jaws of equal length (vs. lower jaw prognathous in T. trachycorystes); skull roof covered by thick (vs. thin) integument; inner mental barbel very thin and short not reaching base of outer barbel (vs. extending to or beyond base of outer mental barbel); dorsal-fin spine serrated posteriorly, smooth or rough anteriorly (vs. serrated anteriorly and smooth or rough posteriorly); caudal fin shallowly forked (vs. emarginate); and gas bladder simple, without diverticula (vs. with three posterior diverticula). Comments and data on the nominal species Trachycorystes trachycorystes are provided. Trachycorystes cratensis Miranda Ribeiro, 1937, is allocated to the genus Trachelyopterus Valenciennes, 1840, and another local catfish species, Parotocinclus aripuanensis Garavello, 1988, has its type locality reassigned.